Price trend of residential property in Kelantan case study: Pengkalan Chepa / Mohd Radhi Mohd Ghazali - Mohd Ghazali, Mohd Radhi (2010)
Housing is an important element in the development of a country. Function and role of home not only acts as a protective agent from weather, night and day and security treats. In modern life now, homes play a main role in the life and produce a people which useful and personality. In Malaysia, the development of housing units can be seen everywhere with various types and new designs introduced in which to provide comfort and options to the public. Then, it also must to meet the need and demand of the population. The increasing people in the state of Kelantan cause the state government has provided provision of conditions that must be followed by interested parties to develop housing schemes for all levels of society could purchase and possession. Although the policies could encourage people buy the houses but the focus of housing for low and middle income group can be settle if the price is suitable for them. A middle group as outlined the Nine Plan, ie those with income households between RM 1,500 and to RM 3,500 .Due to factors of income and eligibility for purchase of medium cost houses and high, they are not able to provide down payment and monthly installments for the house. To realize the dream of middle income group, intensive action needs to be done through the efforts of the government, housing developers and the lenders which is bankJn determining house prices, the government should control the effectives and relaxation of conditions to help low and middle income group in getting a house. Lastly the need a suitable application provided by the bank to the buyer to buy the house.